2018
DOI: 10.1007/s13197-018-3344-2
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and application of chia mucilage (Salvia hispanica L.) and locust bean gum (Ceratonia siliqua L.) in goat milk frozen dessert

Abstract: A complete factorial design (2) was used to determine the influence of chia mucilage concentration (CM), locust bean gum (LBG) and base maturation time (BMT) on 14 formulations of goat milk frozen dessert. Chia mucilage was obtained by chia grain hydration (1:40) under stirring for 2 h, at 80 °C and pH of 9.0. The samples were centrifuged, as well as lyophilised to compare yields. The extraction yield of lyophilised CM was lower than 10%. The addition of LBG and CM at higher levels, influenced by BMT, increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…The addition of fortification substrates to ice cream made from goat milk was addressed by Chaves et al [18]. The substrates evaluated were chia mucilage and bean gum, which both impacted moisture and viscosity.…”
Section: Current Status Of Goat Dairy Productsmentioning
confidence: 99%
“…The addition of fortification substrates to ice cream made from goat milk was addressed by Chaves et al [18]. The substrates evaluated were chia mucilage and bean gum, which both impacted moisture and viscosity.…”
Section: Current Status Of Goat Dairy Productsmentioning
confidence: 99%
“…Currently, there is a growing interest in the development of novel dairy products by substituting cow milk (CM) with milk from other origins. For example, a number of studies are using goat milk (GM) for dairy products such as yogurt, beverage, cheese, frozen dessert and ice cream [1,2,3,4]. This trend may be attributed to the nutritional, health and therapeutic benefits related with GM consumption [5].…”
Section: Introductionmentioning
confidence: 99%
“…Chaves et al. (2018) also observed that the higher concentration of locust bean gum could promote the increase in the moisture content of milk frozen dessert samples (Chaves et al., 2018). Hydrogen bond formed between the polar groups of protein and water is a key factor in water uptake of protein.…”
Section: Resultsmentioning
confidence: 98%
“…The color of control and FFS samples was evaluated by determining three parameters of L*, a*, and b* using Minolta Hunterlab (C360, Japan) through the CIE method. L* represents the lightness, a* represents the redness/greenness quality of the color, and b* represents the yellowness/blueness quality of the color (Chaves et al., 2018).…”
Section: Methodsmentioning
confidence: 99%